2016
DOI: 10.1159/000447299
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Negative Pneumonia Alters Large-Vein Cell-Adhesion Molecule Profile and Potentiates Experimental Stasis Venous Thrombosis

Abstract: Background/Aims: Pneumonia is a significant risk factor for the development of venous thrombosis (VT). Cell-adhesion molecules (CAMs) are linked to the pathogenesis of both pneumonia and VT. We hypothesized that remote infection would confer a prothrombogenic milieu via systemic elevation of CAMs. Methods: Lung injury was induced in wild-type (C57BL/6) mice by lung contusion or intratracheal inoculation with Klebsiella pneumoniae or saline controls. K. pneumoniae-treated mice and controls additionally underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Previous population and registry studies have identified a link between pneumonia and VTE. 2730 This may be due in part to inflammatory and/or infectious stimuli effect on the venous endothelium or simply a reflection of these patients immobility and frailty. Scarborough et al identified VTE events in conjunction with the timing of post-operative complications and found that 5.6% of patients who developed pneumonia subsequently developed a VTE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous population and registry studies have identified a link between pneumonia and VTE. 2730 This may be due in part to inflammatory and/or infectious stimuli effect on the venous endothelium or simply a reflection of these patients immobility and frailty. Scarborough et al identified VTE events in conjunction with the timing of post-operative complications and found that 5.6% of patients who developed pneumonia subsequently developed a VTE.…”
Section: Discussionmentioning
confidence: 99%
“…For blood CFU determinations, blood was collected via cardiac puncture using a sterile 18-gauge needle. To measure bacterial number, 100 μL of undiluted blood was plated onto 5% sheep blood agar plates (Thermo Fisher Scientific) and incubated at 37°C, and then colonies were counted (4,5,49).…”
Section: Methodsmentioning
confidence: 99%
“…In another study using the model of complete IVC stasis, when mice were inoculated with klebsiella pneumoniae to induce pneumonia, they were found to have increased levels of circulating P-selectin. 25 Since elevated sP-selectin is associated with DVT risk and sepsis increases risk for VTE, the role of P-selectin in sepsis associated DVT was explored. When sepsis was induced experimentally in mice with the endotoxin lipopolysaccharide, Pselectin was up-regulated at the vein wall.…”
Section: P-selectinmentioning
confidence: 99%
“…The fact that similar findings have been found in these different models is important, as areas of complete stasis and partial stasis often exist simultaneously in the pathophysiology of clinical DVT. In another study using the model of complete IVC stasis, when mice were inoculated with klebsiella pneumoniae to induce pneumonia, they were found to have increased levels of circulating P‐selectin 25 . Since elevated sP‐selectin is associated with DVT risk and sepsis increases risk for VTE, the role of P‐selectin in sepsis associated DVT was explored.…”
Section: Selectins and Their Ligandsmentioning
confidence: 99%